1979
DOI: 10.1161/01.cir.60.4.921
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the echocardiogram as an epidemiologic tool in an asymptomatic population.

Abstract: An asymptomatic adult population of 196 men and women was studied with the echocardiogram to derive age- and sex-specific "normal" values for a number of clinically used echocardiograhic variables. The results are in general agreement with previously published normal values. Body position during the examination, age and sex influence the echocardiographic results; body surface area correction normalized most of these effects. The prevalence of occult abnormalities determined by the echocardiogram is 7%; the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 21 publications
2
19
2
Order By: Relevance
“…8,14 -18 Ladipo et al, 14 evaluating measurements of 10 blind duplicated tracings by 3 observers, reported intraobserver mean absolute difference of 0.7 to 1.2, 0.2 to 0.8, 0.3 to 0.4, and 0.4 to 0.8 mm for diastolic and systolic LV diameters, diastolic LV posterior wall thickness, and diastolic interventricular septal thickness, respectively. Having 3 investigators measure 7 ventricular parameters of 20 randomly selected echocardiograms twice, Valdez et al 16 showed that significant intraobserver difference was found in only 1 person in the measurement of end-diastolic LV posterior wall thickness. Small means and SDs of intraobserver differences in our study (Table 1) showed that each technician read the same echocardiograms consistently the second time, achieving a high degree of agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,14 -18 Ladipo et al, 14 evaluating measurements of 10 blind duplicated tracings by 3 observers, reported intraobserver mean absolute difference of 0.7 to 1.2, 0.2 to 0.8, 0.3 to 0.4, and 0.4 to 0.8 mm for diastolic and systolic LV diameters, diastolic LV posterior wall thickness, and diastolic interventricular septal thickness, respectively. Having 3 investigators measure 7 ventricular parameters of 20 randomly selected echocardiograms twice, Valdez et al 16 showed that significant intraobserver difference was found in only 1 person in the measurement of end-diastolic LV posterior wall thickness. Small means and SDs of intraobserver differences in our study (Table 1) showed that each technician read the same echocardiograms consistently the second time, achieving a high degree of agreement.…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17][18] De Leonardis and Cinelli 15 compared measurements of aortic root diameter, left atrial diameter, end-diastolic septal and posterior wall thicknesses, and end-diastolic and end-systolic LV diameters by 2 experienced interpreters on 50 routinely performed M-mode echocardiograms and concluded that no significant interobserver variability was found for all measured echocardiographic parameters. Valdez et al 16 found statistically significant differences in measurements of enddiastolic septal thickness, end-diastolic and end-systolic LV posterior wall thicknesses, and end-diastolic and end-systolic LV diameters by 3 observers on 20 echocardiograms. The maximum mean difference was 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…20 In an evaluation of hypertensive subjects participating in the Systolic Hypertension in the Elderly Program (SHEP), Pearson et al found significantly increased LV mass and LA index. 21 Here we have shown the high association of LV hypertrophy and LA enlargement in patients aged 2 60.…”
Section: Left Atrial Enlargement and Hypertensionmentioning
confidence: 99%
“…All available studies agree that LV mass should be indexed by body size, of which body surface area appears to be the best measure by a narrow margin. 4 Similarly, the three largest echocardiographic studies of normal subjects 3 -*•' have found that LV mass indexed by body surface area differs significantly between men and women, and the primary LV measurements reported by Valdez et al 12 . are in accord with this conclusion.…”
mentioning
confidence: 91%